THE ENGLISH DEMOCRATS PARTY IN THE CONTEMPORARY HISTORY OF BRITISH EUROSCEPTICISM - E. Atapin (Гуманитарные и юридические исследования)
«Euroscepticism» is probably the best term to describe the attitude of the United Kingdom towards the European Union in the contemporary history. It is undoubtedly a mul-tifaceted notion connected with many other phenomena of socio-political life. British euroscepticism is tightly related to English nationalism. The English Democrats party combines nationalistic and eurosceptic ideas. Its inception was due to the development and mutual influence of these ideas. The novelty of the study is predetermined by a new subject of research. It is a non-systemic political force which is an appealing ideological platform with a peculiar combination of the principles of English nationalism and British euroscepticism usually not included in the research of recent British history. In addition, the article contains a new approach to the research which is based on identifying the relationship between the concepts of British euroscepticism, British nationalism and English nationalism and characterizing the ideological principles of the English Democrats party through the prism of these concepts. The article provides a brief overview of basic prerequisites for the formation of English nationalism in the second half of the 20th century, detects its relationship with the course of development of British euroscepticism, gives a description of the English Democrats party, and clarifies its role in the history of British euroscepticism. Particular attention is paid to studying the provisions of the manifesto of the English Democrats party regarding its nationalistic and eurosceptic views.